INTERNET USAGE AND JUVENILE DELINQUENCY OF HIGH SCHOOL STUDENTS IN SURABAYA INDONESIA - Indrijati, Herdina; Mastuti, Endah; Prihastuti, Prihastuti (Proceedings of the International Conference on Education, 2018)
This research aimed to find out differences in juvenile delinquency based on the frequency of internet usage on high school students in Surabaya, Indonesia. Internet usage was measured based on the average frequency of daily use of the internet. Juvenile delinquency is students’ tendency to violate regulations which can result in loss and damage both to oneself and others. This research used quantitative approach, involving 498 students from eight different schools in Surabaya, Indonesia. Data collection used internet usage and juvenile delinquency questionnaires. Descriptive statistical analysis and analysis of variance were conducted to analyze the data. The hypothesis testing resulted F coefficient of 3.125 with significance value of 0.026, implying that there were marked differences in juvenile delinquency based on the usage frequency of the internet of high school students in Surabaya Indonesia.